To Tell, or Not to Tell; Confidentiality in an Iranian HIV Positive Patient: A Viewpoint - Mahshad Noroozi; Maliheh Kadivar; Mansure Madani; Pooneh Salari (Tehran University of Medical Sciences, 2017)
Confidentiality is a basic concept in medical ethics and protecting confidentiality is considered as physicians' duty. In some occasions, this protection is in conflict with the right of the patient's sexual partner, who should be informed about the possibility of being infected. The sexual partner being pregnant, the situation is going to be more complicated. In this paper, we present a case discussion with special ethical, legal, social, cultural, and religious aspects. According to this informing sexual partner with the patient's assent, opt-out Human immunodeficiency virus (HIV) screening in pregnant women and enhancing psychosocial and family support are highly recommended. Strategic changes in health system policies and regulations seem to be necessary as well.